The Reality of Teaching Computational Thinking Skills from Viewpoints of Female Computer Teachers in Riyadh City - Alqahtani, Remsh Nasser; Almassaad, Ahmad Zaid (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify computational thinking skills from the perspective of female computer teachers in Riyadh. The study followed the descriptive approach by providing a questionnaire. It consisted of (3) sections, the first: the data of the study sample, the second: the general knowledge of the computer teacher in computational thinking, the third: it consists of (46) phrase to determine the reality of teaching computational thinking skills, divided into (3) axes the first: the use of the computer teacher for computational thinking in solving the problems, the second: teaching computational thinking skills to female students in the computer course, the third: the obstacles that computer teachers face in teaching and using computational thinking skills. It ascertain the validity and applicability of the questionnaire. The questionnaire has been distributed electronically. The sample reached (223) of Computer Teachers in Riyadh. The study found that Computer Teachers have little knowledge about the concept and skills of computational thinking and they strongly agree to use computational thinking in problem - solving during teaching. The Computer Teachers also strongly agree to teach computational thinking skills for students. Teaching dimensions results in following (implementation, evaluation, planning). The study also revealed some obstacles that encounter they face in teaching and using computational thinking skills. The results showed differences in the sample individuals' responses in the axis of teaching computational thinking skills for female students according to academic qualification variable. There were no differences in the sample individuals' responses in all axes according to the number of teaching years' experience variable. There were no differences in the sample individuals' responses in the axis (first and third) according to educational level variable. While, there were differences in the sample individuals' responses in the evaluation dimension of the axis in teaching computational thinking skills for female students between primary and secondary school students for primary ones. There were no differences in the sample individuals' responses in the axes (first and second) according to school type variable. While, there were differences in the sample individuals' responses in the axis of obstacles for the type of governmental school. Several recommendations were presented by researchers such as: providing necessary support to teaching computational thinking skills. Addressing the content of computer curriculum to allow computational thinking skills. Training of female Computer Teachers in- service on appropriate practices for teaching computational thinking skills.
Keywords: Computational Thinking Skills; Female Computer Teachers; Decomposition; Pattern Recognition; Abstraction